Ảnh hưởng của di cư lao động đến cảm nhận về chất lượng sống của người cao tuổi: Nghiên cứu tại tỉnh Long An - Võ Thành, Tâm; Huỳnh Ngọc, Chương (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2017)
Migration trend is normally viewed as an economic phenomenon in many developing economies including Vietnam. A number of previous studies pointed out several negative effects of migration on the left-behind elderly, whose life quality, nevertheless, has not been adequately considered from both academic and policy aspects in the country. This study uses the framework of life quality to measure the impact of migration on the Vietnamese left-behind elderly’s perception of life quality. The results obtained by incorporating quantitative and qualitative approaches in a case study conducted in Long An Province show that migration is a major determinant of life quality of the left-behind elderly, besides such other significant factors as psychological, social, economic, and environmental factors. From the empirical results, the paper suggests some policy implications with respect to: (i) enhancing the role of the elderly in the community; (ii) expanding the welfare and healthcare systems; and (iii) perfecting the living environment for more effective advocacy of their benefits